2020
DOI: 10.1038/s41396-020-00845-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and quantification of anaerobic nitrogen metabolisms among oxygenated tropical Cuban stony corals

Abstract: Coral reef health depends on an intricate relationship among the coral animal, photosynthetic algae, and a complex microbial community. The holobiont can impact the nutrient balance of their hosts amid an otherwise oligotrophic environment, including by cycling physiologically important nitrogen compounds. Here we use 15N-tracer experiments to produce the first simultaneous measurements of ammonium oxidation, nitrate reduction, and nitrous oxide (N2O) production among five iconic species of reef-building coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 99 publications
1
28
0
Order By: Relevance
“…Bacterial taxa involved in other steps of the nitrogen cycle (i.e., nitrification and denitrification) are also more common in those coral species that harbor potential diazotrophs. Several of these taxa that can conduct either, or both, nitrification and denitrification include members of the genus Vibrio, Marinobacter, and Pseudoaltermonas [15,91]. Among the microbiomes of the coral species examined here, members of the genus Endozoicomonas varied in abundance with respect to coral species and traits more than any other microbial genus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bacterial taxa involved in other steps of the nitrogen cycle (i.e., nitrification and denitrification) are also more common in those coral species that harbor potential diazotrophs. Several of these taxa that can conduct either, or both, nitrification and denitrification include members of the genus Vibrio, Marinobacter, and Pseudoaltermonas [15,91]. Among the microbiomes of the coral species examined here, members of the genus Endozoicomonas varied in abundance with respect to coral species and traits more than any other microbial genus.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to freeliving diazotrophs, several important members of the reef community (i.e., corals and sponges) have the capability to fix nitrogen through symbiotic associations with diazotrophs [32,87,88]. It is well-known that the microbiomes of scleractinian corals harbor diazotrophic symbionts [34,35,37,38,41,42], as well as other prokaryotes that mediate transformations of inorganic nitrogen in processes such as nitrification, denitrification, and the anaerobic oxidation of ammonium (ANAMMOX) [11,43,[89][90][91]. For all corals studied here, members of the bacterial phyla Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only the blades of P. scouleri harbored MAGs with both anaerobic and aerobic biosynthetic pathways for Vitamin B 12 , suggesting that the variable oxygen environment driven by host-metabolism creates diverse metabolic niches for associated microbes. Strong gradients in oxygen and metabolically diverse microbial metabolisms are present in a diversity of animal hosts such as corals and sponges as a result of host metabolism (74-76). Fluctuating oxygen microenvironments might also promote cross-feeding, where microbial taxa produce a metabolite that can be consumed by other taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 7, 2022. ; https://doi.org/10.1101/2022.01.05.475171 doi: bioRxiv preprint result of host metabolism (74)(75)(76). Fluctuating oxygen microenvironments might also promote cross-feeding, where microbial taxa produce a metabolite that can be consumed by other taxa.…”
Section: Host-microbe Interactions In a Dynamic Oxygen Microenvironmentmentioning
confidence: 99%
“…Potentially, observed denitrification potential differences among the hard coral species and Xenia sp. occurred due to their different capacity in releasing and producing mucus 96 , 97 , with thick mucus layers favouring high anaerobic potentials that might facilitate denitrification 96 . It has been demonstrated recently that soft coral mucus does not provide a favourable habitat for associated diazotrophs 97 , which in return could explain observed comparatively low N 2 fixation rates.…”
Section: Discussionmentioning
confidence: 99%